GAMBARAN ASUPAN GIZI PADA PENDERITA SINDROM METABOLIK DI RW 04 KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN KOTA PEKANBARU - Rosdiana, Dani; Ernalia, Yanti; Utami, Yurika Utami1 Marthalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diet in major cities was changed from a traditional diet to a Western diet. This was caused by imbalanced food intake and this was a risk factor of many health problems such as obesity, hypertension, dyslipidemia and insulin resistace were known as metabolic syndrome. This study was a descriptive cross-sectional study to determine energy and nutrient intake in patients with metabolic syndrome in RW 04 Kelurahan Sidomulyo Barat Kecamatan Tampan Kota Pekanbaru with 33 peoples as samples and used FFQ (Food Frequency Questionnaire) for data retrieval. The result showed that most of respondents were women (93,94%) and most of them were housewifes (87,88%) and were low education (51,52%). Range the age of them was 32-72 years old and most of them in 40-49 years old (48,49%) and most of them were Minang (51,52%). Most of respondents were high in energy intake ( 97% of total respondents with average intake: 2867 kcal), carbohydrate ( 78,79% of total respondents ), total fat ( 81% of total respondents) and SFA(Saturated Fatty Acid) ( 97% of total respondents ). Most of them were sufficient in consumed MUFA (Monounsaturated Fatty Acid) ( 69,70 % of total respondents ) and in cholesterol intake were sufficient too ( 64 % of total respondents), but the average value of cholesterol intake in respondents was high ( 315 mg ). All respondents consumed sufficient amounts of PUFA (Polyunsaturated Fatty Acid). Most of respondents ( 94 % of total respondents ) were less consumed fiber.Keywords: Metabolic syndrome, energy intake, nutrient intake